2004
DOI: 10.1016/j.cub.2004.03.062
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion-Dependent Regulation of p190RhoGAP in the Developing Brain by the Abl-Related Gene Tyrosine Kinase

Abstract: Abl family kinases, which include the mammalian Abl and Arg (Abl-related gene) kinases, regulate neuronal morphogenesis in developing metazoa (for review, see [1]). Activation of Abl kinase activity directs changes in actin-dependent processes such as membrane ruffling, filopodial protrusion, and cell motility. However, the mechanisms by which increased Abl or Arg kinase activity promote cytoskeletal rearrangements are unclear. We provide evidence that the Rho inhibitor p190RhoGAP (GTPase-activating protein) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
109
1

Year Published

2005
2005
2007
2007

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(114 citation statements)
references
References 18 publications
4
109
1
Order By: Relevance
“…Furthermore, different tyrosine kinases can also phosphorylate and activate another effector of RhoA, p190RhoGAP (11). This protein can be coupled to the adherens junctional complex through its association with p120-catenin (35).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, different tyrosine kinases can also phosphorylate and activate another effector of RhoA, p190RhoGAP (11). This protein can be coupled to the adherens junctional complex through its association with p120-catenin (35).…”
Section: Discussionmentioning
confidence: 99%
“…Arg phosphorylates and activates the Rho inhibitor p190RhoGAP after integrin-mediated adhesion (Hernandez et al, 2004b;Bradley et al, 2006). We monitored FA and stress fiber structure in p190rhogapaϪ/Ϫ (p190Ϫ/Ϫ) and littermate control p190rhogapa ϩ/ϩ (p190 ϩ/ϩ ) fibroblasts expressing YFP or Arg-YFP (Figure 4, C-F).…”
Section: Arg Kinase Activity Acts Through P190rhogap To Inhibit Rho Amentioning
confidence: 99%
“…We previously identified the 190-kDa GTPase-activating protein for Rho (p190RhoGAP) as a major Arg substrate in the developing brain (Hernandez et al, 2004b). Integrin receptor engagement induces Arg-dependent phosphorylation of p190RhoGAP (Hernandez et al, 2004b), which triggers p190RhoGAP localization to the cell membrane where it inhibits Rho activity (Bradley et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Abl kinases regulate a variety of cytoskeletal processes downstream of receptor tyrosine kinases and integrins (9)(10)(11)(12)(13)(14). We have shown that Abl kinases play a role in the regulation of intercellular signals at the neuromuscular junction (NMJ) and at sites of contact between invading bacterial pathogens and mammalian host cells (9,15).…”
mentioning
confidence: 99%